2019
DOI: 10.1111/clr.13441
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of three different implant surface decontamination methods in three different defect configurations

Abstract: Objectives: Evaluation of in vitro efficacy of three different implant surface decontamination methods in a peri-implant bone defect model. Material and methods:A total of 180 implants were stained with indelible red color and distributed to standardized peri-implant bone defect resin models with a circumferential defect angulation of 30°, 60°, or 90° (supraosseous defect). Sixty implants were assigned to each type of defect. All implants were cleaned by the same examiner. For each type of defect, 20 implants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(109 citation statements)
references
References 22 publications
(41 reference statements)
9
99
1
Order By: Relevance
“…While it may be argued that alternative treatment strategies such as air powder abrasion [15] may have been more appropriate as control, it has to be kept in mind that simple, flat surfaces were considered here, which could be well accessed. This is in contrast to clinical reality, where access for removing biofilm due to surface roughness and the macrodesign of implants [25,27] as well as defect morphology [26] is critical. The double diamond electrodes were kept at a distance of 1 mm to the disc surfaces and despite that, they were at least as effective in biofilm removal as the use of curettes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While it may be argued that alternative treatment strategies such as air powder abrasion [15] may have been more appropriate as control, it has to be kept in mind that simple, flat surfaces were considered here, which could be well accessed. This is in contrast to clinical reality, where access for removing biofilm due to surface roughness and the macrodesign of implants [25,27] as well as defect morphology [26] is critical. The double diamond electrodes were kept at a distance of 1 mm to the disc surfaces and despite that, they were at least as effective in biofilm removal as the use of curettes.…”
Section: Discussionmentioning
confidence: 91%
“…The major challenges in peri-implantitis therapy include the risk of changes in implant surface topography [25] due to instrumentation as well as limited access depending on the morphology of the peri-implant defect [26]. Two recent studies pointed out that the complete removal of biofilms from implant surfaces is not feasible due to the macrodesign of the implants [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in all cases, unreached areas were visible (Keim et al, 2019). In the same study, air abrasion showed no surface damage, while sonic scaler and curette damaged the implant surface (Keim et al, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…Mechanical debridement using stainless steel instruments on implant surface causes modifications of the implant surface (Keim et al, 2019;Louropoulou, Slot, & Van der Weijden, 2012), and releases titanium (Ti) particles into the surrounding tissue (Suárez-López Del Amo, Garaicoa-Pazmiño, Fretwurst, Castilho, & Squarize, 2018), which might cause further complications (Eger, Sterer, Liron, Kohavi, & Gabet, 2017, Fretwurst, Nelson, Tarnow, Wang, & Giannobile, 2018. This requires the use of instruments to reduce implant damage while maximizing the cleaning effect (de Tapia et al, 2019;Mann, Parmar, Walmsley, & Lea, 2012;Viganò et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another critical difference in this study was the evaluation of dental plaque on implant surfaces collected in the mouth of participants rather than a single bacterial species [14,20] or artificial biofilms [21,22]. Dental plaque comprises 700-1000 bacterial species and is significantly different to a single bacterial colony or artificial biofilms.…”
Section: Methodsmentioning
confidence: 99%